Beauty queens and battling knights: Risk taking and attractiveness in chess - Anna Dreber; Christer Gerdes; Patrik Gränsmark (Institute for the Study of Labor (IZA), 2010)
We explore the relationship between attractiveness and risk taking in chess. We use a large international panel dataset on chess competitions which includes a control for the players' skill in chess. This data is combined with results from a survey on an online labor market where participants were asked to rate the photos of 626 expert chess players according to attractiveness. Our results suggest that male chess players choose significantly riskier strategies when playing against an attractive female opponent, even though this does not improve their performance. Women's strategies are not affected by the attractiveness of the opponent.
Keywords: D03; J16; 330; risk taking; attractiveness; chess; gender differences